The Eurasian Dry Grassland Group (EDGG) in 2015–2016 - Venn, Stephen; Ambarlı, Didem; Biurrun, Idoia; Dengler, Jürgen; Janišová, Monika; Kuzemko, Anna; Török, Péter; Vrahnakis, Michael (Hacquetia, 2016)
...